Anhydrous calcium sulfate modified resin filler master batch and preparation method thereof
By preparing resin filler masterbatches with high content of anhydrous calcium sulfate, the problem of the low proportion of anhydrous calcium sulfate in granulation is solved, and the performance of composite materials and the utilization rate of anhydrous calcium sulfate are significantly improved.
Patent Information
- Application Number
- CN202510073500.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
AI Technical Summary
Anhydrous calcium sulfate accounts for a low proportion in twin-screw extrusion granulation, resulting in insufficient performance of composite materials and its processing characteristics make it difficult to achieve high proportion filling.
By preparing anhydrous calcium sulfate modified resin filler masterbatch, 70-90% of anhydrous calcium sulfate filler and 9-30% of polymer resin are used, and 0-20% of additives are added to increase the proportion of anhydrous calcium sulfate in granulation.
It improves the rigidity, heat resistance and dimensional stability of composite materials, expands the application scope of anhydrous calcium sulfate, and reduces production costs and environmental pollution.
Smart Images

Figure BDA0005246370980000101
Abstract
Description
Technical Field
[0001] The invention relates to a resin filler masterbatch and a preparation method thereof, and in particular to a modified masterbatch used for resin blending processing and a method thereof. Background Art
[0002] With the development of technology and the rise of economic costs, inorganic fillers are increasingly used in composite materials. When inorganic fillers are used to prepare composite materials, due to the differences in the chemical properties and composition of the fillers, the macroscopic physical form and the resin, they cannot be effectively compatible, and the inorganic fillers are prone to self-agglomeration, which makes it difficult to disperse evenly in the polymer solution, resulting in reduced product performance, and the filler particles are prone to cause dust inhalation to the workers.
[0003] Single polymer resins such as PP, PE (including LDPE, LDPE, HDPE, etc.), PET, ABS, PC, PS, etc., have the characteristics of easy acquisition of raw materials, low material prices, and good fluidity. However, the mechanical properties of a single resin component are poor and cannot meet the actual use requirements. Generally, fillers and additives are often added to meet the relevant performance requirements for application.
[0004] Inorganic fillers and resins can be blended and granulated to improve the performance and stiffness of the material, and play a role in reinforcing and modifying the material. At present, inorganic fillers filled with resins for granulation are mainly calcium carbonate, and anhydrous calcium sulfate is relatively rare.
[0005] Phosphogypsum, as a solid waste generated in the production of phosphoric acid and phosphate fertilizers, has a relatively low effective utilization rate in my country, which not only leads to the occupation of a large amount of land resources, but also easily causes environmental pollution problems. In China, anhydrous calcium sulfate, as a terminal by-product of chemical products, urgently needs to expand its application field. At present, there have been studies on the preparation of masterbatches of anhydrous calcium sulfate to improve the performance of composite materials. However, in view of the processing characteristics of anhydrous calcium sulfate, when the proportion of anhydrous calcium sulfate is high during the process of blending and granulation with resin, it becomes more difficult to prepare pellets. At present, the proportion of anhydrous calcium sulfate in the more mature anhydrous calcium sulfate filler masterbatch will not exceed 50%. Due to the small amount of addition, its effect in reducing production costs and improving product performance is limited. Summary of the invention
[0006] In order to solve the problem of low proportion of anhydrous calcium sulfate in twin-screw extrusion granulation, the present invention provides an anhydrous calcium sulfate modified resin filler masterbatch and a preparation method thereof. The anhydrous calcium sulfate in the anhydrous calcium sulfate filled resin masterbatch prepared by the method has an anhydrous calcium sulfate proportion of more than 50%, which can reach more than 70%, thereby increasing the proportion of anhydrous calcium sulfate in twin-screw extrusion granulation, improving the resin stiffness and dimensional stability, and further expanding the application scope of anhydrous calcium sulfate.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] An anhydrous calcium sulfate modified resin filler masterbatch is prepared by 9-30% polymer resin, 70-90% anhydrous calcium sulfate filler and 0-20% additives by weight percentage. In order to improve processing performance, the ratio of additives to polymer resin can be adjusted to a higher content. In order to ensure cost, rigidity and dimensional stability, the content of anhydrous calcium sulfate filler can be increased, wherein:
[0009] The polymer resin is at least one of PP, PE (including LDPE, LLDPE, HDPE, etc.), PET, ABS, PC, and PS;
[0010] The anhydrous calcium sulfate is a powder processed from phosphogypsum, with a particle size of 500 to 3000 mesh, preferably 1000 to 2000 mesh, and a purity of 90 to 99%;
[0011] The auxiliary agent includes at least one of a lubricant, a dispersant, and a coupling agent;
[0012] The lubricant includes at least one of hydrocarbon lubricants (such as microcrystalline wax, polyethylene wax, oxidized polyethylene wax, Fischer-Tropsch wax, paraffin, etc.), fatty acid lubricants (such as stearic acid, hydroxystearic acid), fatty alcohol lubricants (such as stearyl alcohol, pentaerythritol, etc.), fatty acid ester lubricants (PETS, glyceryl monostearate, glyceryl polystearate, etc.), fatty amide lubricants (such as EBS, oleamide, stearamide, butyl stearate, glyceryl trihydroxystearate, etc.), metal soap lubricants (such as zinc stearate, calcium stearate, magnesium stearate, etc.), polyethylene, fatty acid soap lubricants, PPA, EBS, barium stearate, TAF, EVA wax, erucic acid amide, and PEG, preferably including at least one of zinc stearate, calcium stearate, paraffin, stearic acid, and polyethylene wax;
[0013] The dispersant comprises at least one of white oil (liquid paraffin), solid paraffin, dioctyl phthalate (DOP), low molecular weight polyethylene (polyethylene wax), stearic acid, fatty acid soap dispersants, fatty amide dispersants, oxidized polyethylene wax, sodium dodecylbenzene sulfonate, polyethylene glycol (PEG), polyvinyl alcohol, polyvinyl ester, polyacrylate, polypropylene alcohol, silicate dispersants (sodium silicate), phosphate dispersants (sodium tripolyphosphate), ethanol, propanol, starch, cellulose derivatives, PP wax, sodium dodecylbenzene sulfonate, dodecyl acetic acid, polyester, acrylate polymer dispersants, polyurethane or polyester dispersants, preferably at least one of PP wax, PE wax, white oil, stearic acid and EVA wax;
[0014] The coupling agent is at least one of a silane coupling agent (such as KH550, KH560, KH570, KH792), an organic silane coupling agent, an organic titanate coupling agent, an aluminate coupling agent, a metal composite coupling agent, a phosphate coupling agent, a borate coupling agent, a lignin coupling agent, and isopropyl trioleyl titanate, preferably at least one of KH-560, an organic titanate coupling agent, an aluminate coupling agent, and isopropyl trioleyl titanate.
[0015] A method for preparing the above-mentioned anhydrous calcium sulfate modified resin filler masterbatch comprises the following steps:
[0016] Step (1) weighing the resin, anhydrous calcium sulfate filler and additives according to the above weight percentages;
[0017] Step (2) mixing the resin, anhydrous calcium sulfate filler and additives in an internal mixer or a kneader at a mixing temperature of 120 to 230° C., preferably 120 to 200° C., and a mixing time of 5 to 30 min, preferably 5 to 15 min;
[0018] Step (3) putting the uniformly mixed materials in step (2) into an extrusion device for extrusion granulation, wherein: the extrusion device is a twin-screw extruder or a single-screw extruder, the mixing screw speed is 1 to 600 rpm, preferably 20 to 100 r / min; 1 to 4 temperature zones are set, the extrusion temperature is 120 to 230° C., preferably 120 to 200° C.; the aspect ratio is 20 to 50, the compression ratio is 1.2 to 5; the working pressure is 0 to 40 bar;
[0019] Step (4) The material is cooled and shaped after extrusion, and pelletized to obtain anhydrous calcium sulfate filled resin masterbatch, wherein: the cooling temperature is 18-35° C., the masterbatch diameter is 3-5 mm, and the rotation speed is 0-800 rpm.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] 1. The present invention uses anhydrous calcium sulfate to fill the resin, which can improve the rigidity of the product. Compared with the composite material prepared by filling the resin with talcum powder filler, the tensile strength of the composite material can be increased from 13MPa to 15MPa, so that the strength of the product is improved to a certain extent.
[0022] 2. The present invention uses anhydrous calcium sulfate to fill the resin, which can improve the heat resistance of the product. The inorganic filler has high heat resistance, and using it to granulate and prepare composite materials can significantly improve the heat resistance of the product.
[0023] 3. The present invention uses anhydrous calcium sulfate to fill the resin, which can improve the dimensional stability of the product. After adding the inorganic filler, the shrinkage rate of the plastic can be greatly reduced, thereby improving the dimensional stability of the product.
[0024] 4. The anhydrous calcium sulfate in the anhydrous calcium sulfate filled resin masterbatch prepared by the present invention accounts for more than 50%, and can reach more than 70%. The anhydrous calcium sulfate used is a by-product of phosphogypsum, and its source is abundant. It greatly improves the utilization rate of phosphogypsum, reduces production costs, alleviates environmental pollution, and has obvious economic benefits.
[0025] 5. The masterbatch prepared by the present invention can be blended with resin fillers to prepare plates and sheets, which can be used for forming products such as vacuum forming, blow molding, injection molding, and compression molding.
[0026] 6. The present invention combines an internal mixer with a single / twin screw extruder to perform material blending and granulation, which is simple to operate and the prepared anhydrous calcium sulfate filled resin masterbatch is stable and uniform. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0028] Example 1
[0029] This embodiment provides a method for preparing anhydrous calcium sulfate modified resin filler masterbatch, wherein anhydrous calcium sulfate is filled into the resin, and other additives are added to prepare the masterbatch, and the specific steps are as follows:
[0030] Step (1) taking materials: taking the following raw materials according to the weight ratio: 21 parts of LDPE masterbatch, 78 parts of anhydrous calcium sulfate filler, 0.6 parts of PE wax (dispersant), 0.3 parts of zinc stearate (lubricant), and 0.1 parts of KH-560 (coupling agent);
[0031] Step (2) mixing the materials: mixing LDPE masterbatch, anhydrous calcium sulfate, PE wax, zinc stearate and KH-560, and mixing them in a 120° C. internal mixer for 15 minutes until the materials are mixed evenly;
[0032] Step (3) using a twin-screw extrusion granulation: feeding the mixed material into the feed port of the twin-screw extruder and extruding at 120° C. and 40 r / min;
[0033] Step (4) granulation: after being extruded by a twin-screw extruder, the material is pulled to a place where there is natural flowing water (20-30° C.) and natural wind for water cooling and air cooling to shape the material, and then granulated to obtain a mixed masterbatch.
[0034] Experimental phenomenon: There is too much calcium sulfate powder, which is not fully mixed with other materials, and the materials cannot be fully kneaded and evenly mixed.
[0035] Embodiment 2:
[0036] This embodiment provides a method for preparing anhydrous calcium sulfate modified resin filler masterbatch, wherein anhydrous calcium sulfate is filled into the resin, and other additives are added to prepare the masterbatch, and the specific steps are as follows:
[0037] Step (1) taking materials: taking the following raw materials according to weight ratio: 21 parts of LDPE masterbatch, 78 parts of anhydrous calcium sulfate filler, 0.6 parts of PE wax, 0.3 parts of zinc stearate, and 0.1 parts of KH-560;
[0038] Step (2) mixing the materials: mixing LDPE masterbatch, anhydrous calcium sulfate, PE wax, zinc stearate and KH-560, and mixing them in a 150° C. internal mixer for 15 minutes until the materials are mixed evenly;
[0039] Step (3) using a twin-screw extrusion granulation: feeding the uniformly kneaded material into the feed port of the twin-screw extruder, and extruding at 150° C. and 40 r / min;
[0040] Step (4) granulation: after being extruded by a twin-screw extruder, the material is pulled to a place where there is natural flowing water (20-30° C.) and natural wind for water cooling and air cooling to shape the material, and then granulated to obtain a mixed masterbatch.
[0041] Experimental phenomenon: The material is evenly dispersed, the surface of the product is smooth and uniform, and it can be extruded and granulated; the properties of the masterbatch are shown in Table 1.
[0042] Example 3
[0043] This embodiment provides a method for preparing anhydrous calcium sulfate modified resin filler masterbatch, wherein anhydrous calcium sulfate is filled into the resin, and other additives are added to prepare the masterbatch, and the specific steps are as follows:
[0044] Step (1) taking materials: taking the following raw materials according to weight ratio: 21 parts of LDPE masterbatch, 78 parts of anhydrous calcium sulfate filler, 0.6 parts of PE wax, 0.3 parts of zinc stearate, and 0.1 parts of KH-560;
[0045] Step (2) mixing the materials: mixing LDPE masterbatch, anhydrous calcium sulfate, PE wax, zinc stearate and KH-560, and mixing them in a 150° C. internal mixer for 10 minutes until the materials are mixed evenly;
[0046] Step (3) using a twin-screw extrusion granulation: feeding the mixed material into the feed port of the twin-screw extruder and extruding at 180° C. and 40 r / min;
[0047] Step (4) granulation: after being extruded by a twin-screw extruder, the material is pulled to a place where there is natural flowing water (20-30° C.) and natural wind for water cooling and air cooling to shape the material, and then granulated to obtain a mixed masterbatch.
[0048] Experimental phenomenon: blending is possible, the processing time is short, the material dispersion effect is moderate, the surface smoothness and dispersion degree are not as good as those in Example 2; extrusion granulation is possible.
[0049] Example 4
[0050] This embodiment provides a method for preparing anhydrous calcium sulfate modified resin filler masterbatch, wherein anhydrous calcium sulfate is filled into the resin, and other additives are added to prepare the masterbatch, and the specific steps are as follows:
[0051] Step (1) taking materials: taking the following raw materials according to weight ratio: 17 parts of LDPE masterbatch, 82 parts of anhydrous calcium sulfate filler, 0.6 parts of PE wax, 0.3 parts of zinc stearate, and 0.1 parts of KH-560;
[0052] Step (2) mixing the materials: mixing LDPE masterbatch, anhydrous calcium sulfate, PE wax, zinc stearate and KH-560, and mixing them in a 150° C. internal mixer for 15 minutes until the materials are mixed evenly;
[0053] Step (3) using a twin-screw extrusion granulation: feeding the mixed material into the feed port of the twin-screw extruder and extruding at 200° C. and 40 r / min;
[0054] Step (4) granulation: after being extruded by a twin-screw extruder, the material is pulled to a place where there is natural flowing water (20-30° C.) and natural wind for water cooling and air cooling to shape the material, and then granulated to obtain a mixed masterbatch.
[0055] Experimental phenomenon: can be dispersed, the effect is average, and the internal distribution of the material is average.
[0056] Example 5
[0057] This embodiment provides a method for preparing anhydrous calcium sulfate modified resin filler masterbatch, wherein anhydrous calcium sulfate is filled into the resin, and other additives are added to prepare the masterbatch, and the specific steps are as follows:
[0058] Step (1) taking materials: taking the following raw materials according to weight ratio: 17 parts of LDPE masterbatch, 82 parts of anhydrous calcium sulfate filler, 0.6 parts of PE wax, 0.3 parts of zinc stearate, and 0.1 parts of KH-560;
[0059] Step (2) mixing the materials: mixing LDPE masterbatch, anhydrous calcium sulfate, PE wax, zinc stearate and KH-560, and mixing them in a 150° C. internal mixer for 30 minutes until the materials are mixed evenly;
[0060] Step (3) using a twin-screw extrusion granulation: feeding the uniformly kneaded material into the feed port of the twin-screw extruder, and extruding at 150° C. and 40 r / min;
[0061] Step (4) granulation: after being extruded by a twin-screw extruder, the material is pulled to a place where there is natural flowing water (20-30° C.) and natural wind for water cooling and air cooling to shape the material, and then granulated to obtain a mixed masterbatch.
[0062] Experimental phenomenon: The materials are mixed evenly and the surface of the product is uniform; the dispersion effect is good and granulation is possible; the properties of the masterbatch are shown in Table 1.
[0063] Example 6
[0064] This embodiment provides a method for preparing anhydrous calcium sulfate modified resin filler masterbatch, wherein anhydrous calcium sulfate is filled into the resin, and other additives are added to prepare the masterbatch, and the specific steps are as follows:
[0065] Step (1) taking materials: taking the following raw materials according to weight ratio: 13 parts of LDPE masterbatch, 86 parts of anhydrous calcium sulfate filler, 0.6 parts of PE wax, 0.3 parts of zinc stearate, and 0.1 parts of KH-560;
[0066] Step (2) mixing the materials: mixing LDPE masterbatch, anhydrous calcium sulfate, PE wax, zinc stearate and KH-560, and mixing them in a 150° C. internal mixer for 30 minutes until the materials are mixed evenly;
[0067] Step (3) using a twin screw for extrusion granulation: feeding the evenly kneaded material into the feed port of the twin screw, and extruding at 120-200° C. and 40 r / min;
[0068] Step (4) granulation: after being extruded by a twin-screw extruder, the material is pulled to a place where there is natural flowing water (20-30° C.) and natural wind for water cooling and air cooling to shape the material, and then granulated to obtain a mixed masterbatch.
[0069] Experimental phenomenon: Directly kneaded materials cannot be mixed and remain in powder form; they need to be kneaded at 150°C for 30 minutes, then the temperature is raised to 200°C for blending for 10 minutes, and then the blending extrusion granulation can be implemented to ensure uniform mixing.
[0070] Example 7
[0071] This embodiment provides a method for preparing anhydrous calcium sulfate modified resin filler masterbatch, wherein anhydrous calcium sulfate is filled into the resin, and other additives are added to prepare the masterbatch, and the specific steps are as follows:
[0072] Step (1) taking materials: taking the following raw materials according to weight ratio: 10 parts of LDPE masterbatch, 9 parts of HDPE masterbatch, 80 parts of anhydrous calcium sulfate filler, 0.6 parts of PE wax, 0.3 parts of zinc stearate, and 0.1 parts of KH-560;
[0073] Step (2) mixing the materials: mixing LDPE masterbatch, anhydrous calcium sulfate, PE wax, zinc stearate and KH-560, and mixing them in a 150° C. internal mixer for 30 minutes until the materials are mixed evenly;
[0074] Step (3) using a twin-screw extrusion granulation: feeding the mixed material into the feed port of the twin-screw extruder and extruding at 120° C. and 40 r / min;
[0075] Step (4) granulation: after being extruded by a twin-screw extruder, the material is pulled to a place where there is natural flowing water (20-30° C.) and natural wind for water cooling and air cooling to shape the material, and then granulated to obtain a mixed masterbatch.
[0076] Experimental phenomenon: The materials are evenly mixed and the surface of the product is uniform; the dispersion effect is good and granulation is possible; the properties of the masterbatch are shown in Table 1.
[0077] Example 8
[0078] This embodiment provides a method for preparing anhydrous calcium sulfate modified resin filler masterbatch, wherein anhydrous calcium sulfate is filled into the resin, and other additives are added to prepare the masterbatch, and the specific steps are as follows:
[0079] Step (1) taking materials: taking the following raw materials according to the weight ratio: 16 parts of LDPE masterbatch + HDPE masterbatch, the weight ratio of LDPE masterbatch to HDPE masterbatch is 9:6, 83 parts of anhydrous calcium sulfate filler, 0.6 parts of PE wax, 0.3 parts of zinc stearate, and 0.1 parts of KH-560;
[0080] Step (2) mixing the materials: mixing LDPE masterbatch, anhydrous calcium sulfate, PE wax, zinc stearate and KH-560, and mixing them in a mixer at 200° C. for 5 minutes until the materials are mixed evenly;
[0081] Step (3) using a twin-screw extrusion granulation: feeding the mixed material into the feed port of the twin-screw extruder, and extruding at a temperature of 150° C. and 40 r / min;
[0082] Step (4) granulation: after being extruded by a twin-screw extruder, the material is pulled to a place where there is natural flowing water (20-30° C.) and natural wind for water cooling and air cooling to shape the material, and then granulated to obtain a mixed masterbatch.
[0083] Experimental phenomenon: The materials are mixed evenly and the surface of the product is uniform; the dispersion effect is good and granulation is possible; the properties of the masterbatch are shown in Table 1.
[0084] Example 9
[0085] The difference between this embodiment and embodiments 1-8 is that the resin is a blend of LDPE, LLDPE, HDPE and PP.
[0086] Table 1
[0087]
Claims
1. An anhydrous calcium sulfate modified resin filler masterbatch, characterized in that The master batch is prepared from 9-30% of polymer resin, 70-90% of anhydrous calcium sulfate filler and 0-20% of auxiliary agent in weight percentage, and the particle size of the anhydrous calcium sulfate is 500-3000 meshes.
2. The calcium modified resin filler masterbatch according to claim 1, characterized in that The anhydrous calcium sulfate is processed from phosphogypsum, and the particle size is preferably 1000-2000 mesh; the resin includes at least one of PP, PE, PET, ABS, PC, and PS; the additive includes at least one of a lubricant, a dispersant, and a coupling agent.
3. The calcium modified resin filler masterbatch according to claim 2, characterized in that The lubricant includes at least one of hydrocarbon lubricants, fatty acid lubricants, fatty alcohol lubricants, fatty acid ester lubricants, fatty amide lubricants, metal soap lubricants, polyethylene, fatty acid soap lubricants, PPA, EBS, barium stearate, TAF, EVA wax, erucic acid amide, and PEG; the dispersant includes liquid paraffin, solid paraffin, DOP, polyethylene wax, stearic acid, fatty acid soap dispersant, fatty amide dispersant, oxidized polyethylene wax, sodium dodecylbenzene sulfonate, PEG, polyvinyl alcohol, polyethylene The invention relates to a method for preparing the present invention which comprises the following steps: the step of preparing the present invention comprises: preparing the present invention comprises at least one of esters, polyacrylates, polypropylene alcohols, silicate dispersants, phosphate dispersants, ethanol, propanol, starch, cellulose derivatives, PP wax, sodium dodecylbenzene sulfonate, dodecylacetic acid, polyester, acrylate polymer dispersants, polyurethane or polyester dispersants; the coupling agent comprises at least one of silane coupling agents, organic silane coupling agents, titanate coupling agents, aluminate coupling agents, metal composite coupling agents, phosphate coupling agents, borate coupling agents, lignin coupling agents and isopropyl trioleyl titanate.
4. The calcium modified resin filler masterbatch according to claim 3, characterized in that The lubricant preferably includes at least one of zinc stearate, calcium stearate, paraffin, stearic acid, and polyethylene wax.
5. The calcium modified resin filler masterbatch according to claim 3, characterized in that The dispersant preferably includes at least one of PP wax, PE wax, white oil, stearic acid, and EVA wax.
6. The calcium modified resin filler masterbatch according to claim 3, characterized in that The coupling agent preferably includes at least one of KH-560, an organic titanate coupling agent, an aluminate coupling agent, and isopropyl trioleyl titanate.
7. A method for preparing the calcium-modified resin filler masterbatch according to any one of claims 1 to 6, characterized in that The method comprises the following steps: Step (1) weighing resin, anhydrous calcium sulfate filler, and additives; Step (2) mixing the resin, anhydrous calcium sulfate filler and additives in an internal mixer or a kneader at a mixing temperature of 120 to 230° C. for a mixing time of 5 to 30 min; Step (3) putting the uniformly mixed materials of step (2) into an extrusion device for extrusion granulation, wherein: the mixing screw speed is 1 to 600 rpm, and the extrusion temperature is 120 to 230° C.; In step (4), the material is cooled and shaped after extrusion, and pelletized to obtain anhydrous calcium sulfate filled resin masterbatch.
8. The method for preparing the calcium modified resin filler masterbatch according to claim 7, characterized in that The mixing temperature is preferably 120-200° C., and the mixing time is preferably 5-15 minutes.
9. The method for preparing the calcium modified resin filler masterbatch according to claim 7, characterized in that The extrusion equipment is a twin-screw extruder or a single-screw extruder, the mixing screw speed is preferably 20-100 r / min; 1-4 temperature zones are set, the extrusion temperature is preferably 120-200° C.; the aspect ratio is 20-50, the compression ratio is 1.2-5; and the working pressure is 0-40 bar.
10. The method for preparing calcium modified resin filler masterbatch according to claim 7, characterized in that The cooling temperature is 18-35° C., the masterbatch diameter is 3-5 mm, and the rotation speed is 0-800 rpm.